THE FIRE SAFETY TRAINING OF THE PRIMERY SCHOOL CHILDREN: MODERN STATE OF THE PROBLEM - Oleksandr Cherkashyn (Ternopil Volodymyr Hnatiuk National Pedagogical University, 2016)
In the article the informative material which is based on the fire safety is studied and the effectiveness of its use in the educational process of younger students is evaluated. The attention is focused on the compliance of its content for a practical way usage by students in terms of professional readiness for self-defence. Author's textbook on challenges of teaching children of primary school age fire safety is reviewed. On the basis of educational-methodical and scientific literature analysis, the conclusions about the systematization and the need for a unified approach to solving the designated problems, and developing a new system of organization of teaching children the basics of fire safety that requires a more thorough scientific understanding were made. The causes of the ignorance by younger students the basics of fire safety were revealed and methodical recommendations for improving the formation of their fire prevention knowledge were elaborated.